Isolated ocular relapse in pediatric acute lymphoblastic leukemia: a case report - Van Aerschot, Joseph; Goes, Stéphanie; Casteels, Ingele; Segers, Heidi; Cassiman, Catherine (Digital Journal of Ophthalmology, 2026)
A 5-year-old girl, previously in complete remission from common B-cell acute lymphoblastic leukemia (B-ALL), presented at the University Hospital of Leuven with a unilateral, painless red left eye. Over several weeks, the clinical picture evolved from common conjunctivitis into a painful red eye with iris heterochromia and increased iris vascularization unresponsive to topical and oral antibiotics. No signs of leukemic relapse were detected on comprehensive systemic work-up, including bone marrow and lumbar puncture. Aqueous sampling at this time could not confirm the clinical suspicion of isolated ocular relapse of ALL. Oral prednisolone was initiated, with good clinical response. After discontinuation of steroids, the affected eye developed a hypopyon-like mass in the anterior chamber. Urgent anterior chamber washout was performed. Cytology now confirmed the presence of a leukemic infiltrate, indicating an isolated ocular relapse of common B-ALL. Not only because this was the fourth relapse, but primarily because this patient had already undergone extensive prior treatments, including an allogeneic stem cell transplant just 6 months earlier, there were no systemic therapeutic options available. Palliative radiotherapy to the left orbit was therefore initiated. Two months later, the girl presented with similar symptoms in the right eye, which was also treated with radiotherapy.